مساهمة المستشرقين في تأسيس قواعد كتابة التاريخ الإسلامي الحديث عبر المكتبات الغربية (أرشفة الإسلام). - خضر صلاح مهدي ال&#1606 (Journal of Babylon Center for Humanities Studies, 2026)
this research aims to highlight the pivotal role played by Orientalists in shaping the foundations of modern Islamic historiography through their intensive efforts in collecting and archiving Islamic manuscripts in Western libraries from the 18th to the early 20th century. Through both individual and institutional endeavors, Orientalists established an extensive archive of Islamic texts-spanning Hadith, jurisprudence, history, biography, and genealogy-enabling the construction of new historical narratives that often diverged from traditional Islamic perspectives. The study explores key institutions involved in this process, such as the British Library in London, the Bibliothèque nationale de France in Paris, and the Berlin State Library. It analyzes how the cataloguing, selective translation, and editorial framing of Islamic texts often served to reinforce preconceived notions about Islamic history and civilization. A critical question raised by the research is the methodological bias inherent in the archival process, particularly the selective inclusion of texts and their presentation outside their original religious and cultural contexts. Using a critical-analytical methodology, the study draws upon Orientalists' archives, correspondences, and institutional histories- particularly the emergence of Oriental Studies departments in Western academia. It also examines the paradox whereby Muslim scholars themselves came to rely heavily on these archives, thus indirectly adopting Orientalist perspectives in their own historiographical efforts. The research concludes that while these archival projects were framed as scholarly and objective, they were often infused with cultural and colonial assumptions. This necessitates a re-reading of the archived material with a critical lens that re-centers Islamic sources and contexts, while simultaneously recognizing the mechanisms through which Western academic structures have influenced the modern understanding of Islamic history.